- #1
filip97
- 31
- 0
I read Aczel book "Lectures of functional equations an their applications".
On page 223. (Sincov's equation) is equation :
##F(x,y)+F(y,z)=F(x,z)##
and general solution of this
##F(x,y)=g(x)−g(y)##
, but how I prove that this function satisfies conditions
##F(x,y)=F(0,y−x)##
??
On page 223. (Sincov's equation) is equation :
##F(x,y)+F(y,z)=F(x,z)##
and general solution of this
##F(x,y)=g(x)−g(y)##
, but how I prove that this function satisfies conditions
##F(x,y)=F(0,y−x)##
??